1994
DOI: 10.1530/jrf.0.1000497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the presence of male and female flockmates on reproductive activity in ewes

Abstract: Four experiments were carried out to determine the effect of the presence of ewes and rams on the reproductive state of ewes. In Expt 1, the breeding season of ewes kept with a vasectomized ram ended later (April 18 \ m=+-\ 8 days; mean \ m=+-\ sem) than that of ewes isolated from rams (6 March \ m=+-\ 7 days; P < 0.01). In Expt 2, the end of the breeding season was later (5 May \ m=+-\ 6 days; P < 0.05) and the onset of the next breeding season earlier (29 September \ m=+-\ 2 days; P < 0.001) in ewes maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…In this study, most Suffolk ewes that joined an intact ram 5 weeks onward after the beginning of melatonin feeding showed the estrous onset about 3 weeks after the beginning of the joining. Such response seen in ewes fed melatonin is similar to the reproductive response in Suffolk and its cross ewes that joined a ram without melatonin in early August during the late anestrous season [16,17]. In addition, intervals from the ram introduction to the incidence of estrus in Sub-groups A, B and C ewes fed melatonin and control ewes were similar to each other, although the incidence of estrus in the latter was significantly lower than the former.…”
Section: Resultssupporting
confidence: 61%
“…In this study, most Suffolk ewes that joined an intact ram 5 weeks onward after the beginning of melatonin feeding showed the estrous onset about 3 weeks after the beginning of the joining. Such response seen in ewes fed melatonin is similar to the reproductive response in Suffolk and its cross ewes that joined a ram without melatonin in early August during the late anestrous season [16,17]. In addition, intervals from the ram introduction to the incidence of estrus in Sub-groups A, B and C ewes fed melatonin and control ewes were similar to each other, although the incidence of estrus in the latter was significantly lower than the former.…”
Section: Resultssupporting
confidence: 61%
“…This result does not agree with the findings of Thimonier and Maulé on (1969) who, in the same breed, detected considerable levels of ovulatory activity in April to May. There are two possible explanations for this difference: (i) in our experiment, we used concentrations of progesterone to define anoestrus, whereas they used direct laparoscopic observation of ovulation and (ii) in our experiment, ewes were completely isolated from rams, whereas in their study rams were continuously present in the flock and used to detect spontaneous oestrus and the presence of rams may have modified the endogenous pattern of seasonality (O'Callaghan et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, the mixing of cyclic and anoestrous ewes can induce a synchronized ovulation in the anoestrous ewes, a phenomenon called the 'female effect'. This effect is well known and effective in goats (Restall et al, 1995), but it is more controversial in sheep (Nugent and Notter, 1990;O'Callaghan et al, 1994;Zarco et al, 1995). This effect, if real in sheep, could interfere with the response to the 'ram effect' and its effect would vary depending on the proportion of spontaneously ovulating females in the flock.…”
Section: Discussionmentioning
confidence: 99%
“…Kennaway et al (1987) found that when ewes that had an advanced breeding season following treatment with melatonin were maintained in physical contact with anoestrous ewes, the onset of reproductive activity occurred earlier in these ewes than in isolated controls. Also O'Callaghan et al (1994) reported that in housed ewes under controlled photoperiod, effects of oestrous ewes on flockmate anoestrous ewes were obtained, indicating that female-female social interactions can play a role in the timing of reproductive transitions in ewes. This fact is of considerable importance for farmers since the treatment of half of the flock could be sufficient to increase reproductive efficiency of the entire flock.…”
Section: Groupmentioning
confidence: 95%